A Rapid LAMP-Based Method for Screening Poultry Samples for Campylobacter Without Enrichment - Romero, M. Rosario; Cook, Nigel (Frontiers in Microbiology, 2018)
Campylobacter is the most prominent bacterium associated with foodborne disease and the majority of human infection cases are attributed to chicken. Rapid methods capable of determining the Campylobacter status of poultry products in a short time are needed in today’s fast-paced food supply chain. In this study, we developed and evaluated an easy to perform, rapid and robust method for direct detection of Campylobacter in poultry carcasses based on Loop-mediated isothermal DNA AMPlification (LAMP). The method does not require bacterial culture or DNA purification and generates results in just an hour. A total of 171 swabs from chicken and turkey slaughter houses were analysed in parallel by both LAMP and conventional culture-based enumeration methods to evaluate the performance of the rapid method. Campylobacter was detected by LAMP in 100 % of swabs with an enumeration result of ≥800 cfu/swab, and 98.6 % (69 out of 70) of samples reported as negative by enumeration (≤10cfu/swab) were also negative by LAMP. The method is also suitable for analysis of boot swabs from poultry houses, and therefore it represents a convenient screening tool that can be implemented on farm, at slaughter houses, processing plants or retail, to help with the control of Campylobacter contamination throughout the food supply chain. The inclusion of an internal amplification control prevents any potential false negative results due to DNA amplification inhibitors that might be present in the sample.